ANALYSIS OF ENSURING THE SAFETY OF FREIGHT WAGON IN MODERN CONDITIONS OF OPERATION (Transport systems and technologies, 2021)
The current state of the freight wagon fleet is characterized by increased physical wear over time. Disproportionate renewal of rolling stock, low quality of repair due to the lack of appropriate modernization of production systems, the peculiarities of loading and unloading operations in operation make increased demands on the preservation of the wagon fleet. The issues of general management of the transport safety system deserve special attention. Control of safety of freight wagons should be carried out at all stages of operation: at freight works, at transfer in the international and domestic communication, at maintenance and repair. In this case, each stage requires the use of appropriate regulations, which ensures compliance with the conditions of storage of freight wagons in operation.The presented article analyzes the current state of the freight wagon fleet with a view to ensuring their safety during operation. The factors that are the most influential in terms of effective management of the wagon fleet are identified. Possible conservation strategies are considered. The statistical material on failures and damages of wagons is resulted. Based on this, an assessment of the most significant events in terms of the impact on ensuring the safety of wagons was made. Practical solutions for creating an effective system for preserving rolling stock in transport are proposed.
Keywords: safety of wagons, railway infrastructure, transportation process, damage to wagons, wagon fleet.